Semantic Models for the Translation of Greek Institutional Terms in the Field of Education - Kassapi, Eleni (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis article takes under consideration a notorious problem area for Greek < > Italian and Spanish <> Greek translators, caused by the gap of standardized international academic terminology, a situation that creates incongruity: 1) between the Italian and the Greek terms and 2) between the Spanish and the Greek terms, as Greek institutional academic terms have potential Italian and Spanish equivalents with a similar core but different edges.